Hubungan Tepat Pasien Terhadap Tepat Dosis Antibiotik ISPA pada Balita di Puskesmas Banjarbaru Utara Periode Tahun 2022 - Baiq Nurdiana Ulfa; Karunita Ika Astuti; Helmina Wati (Universitas Borneo Lestari, 2023)
Acute Respiratory Infection (ARI) is a pathological condition characterized by the invasion of microorganisms, namely bacteria and viruses, into the respiratory tract of human individuals. The misuse of antibiotics can result in the development of antibiotic resistance. The objective of this study is to assess the appropriate patient selection and dosage determination as well as investigate the correlation between patient selection and dosage of ARI antibiotics in toddlers attending the North Banjarbaru Health Center. The present study is a retrospective, non‐experimental investigation that examined patient medical records from January to April 2023. The sample consisted of 184 individuals who satisfied the predetermined inclusion and exclusion criteria. According to the findings of the research, the utilization of ARI antibiotics was characterized by the prevalence of Cotrimoxazol 85 (46.19%), followed by Amoxicillin 67 (36.41%), and Cefadroxil 32 (17.40%). The patients were evaluated accurately in 184 cases, representing 100% of the total. The correct dosage was administered in 155 instances, accounting for 84.2% of the total, while an incorrect dosage was administered in 29 cases, representing 15.8% of the total. The statistical analysis using the Mann‐Whitney test indicated that there was no significant relationship between the appropriate patient selection and the correct dosage administration, as evidenced by a p‐value greater than 0.05 (p = 1.000). The study findings indicated a lack of correlation between the appropriate patient selection and the correct dosage of ARI antibiotics administered to toddlers at the North Banjarbaru Health Center.